Economic Complexity and Human Development in MENA Countries: A Panel ARDL Analysis - Benhamed, Adel; Abdennour, Faouzi (Journal of Posthumanism, 2025)
Economic complexity has become a hot new topic in recent decades. Economic complexity reflects the amount of know-how embedded in an economy’s productive structure. The primary purpose of this research is to comprehend the relationship between economic complexity and human development in 13 Middle East and North Africa (MENA) countries from 1998 to 2021. Using a Panel Autoregressive Distributed Lag Model (ARDL) model, the econometric results proved that there is a stable statistically significant long-run relationship between Economic Complexity and Human Development. More economic complexity generates greater standard of living which, engenders more education, better health care and better social services.